Inside Out: A Novel Labral Repair and Advancement Technique - Mei-Dan, Omer (Elsevier, 2014)
Labral tears are a significant cause of hip pain and are currently the most common indication for hip arthroscopy. Compared with labral debridement, labral repair has significantly better outcomes in terms of both daily activities and athletic pursuits in the setting of femoral acetabular impingement. The techniques described in the literature all use anchor placement on the capsular aspect of the acetabular rim, which can be difficult especially anteriorly, where the rim is very thin, and has the potential for significant complications. Anchor breakage, anchor slippage into the surrounding (capsular side) soft tissue, and penetration of the cartilage surface are among the most common complications. We describe an intra-articular anchor placement technique for labral repair from inside out. This technique, because of the location of the anchor and direction of suture pull, can assist in labral advancement in cases in which the native labrum fails to create a seal because of its location away from the femoral head.